Fungicidal and trypanocidal activity of aqueous extracts of leaves and inflorescences of Verbesina macrophylla (Asteraceae) - Bezerra, Laís de Almeida; Carvalho, Lais Pessanha; Mello, Érica de Oliveira; Taveira, Gabriel Bonan; Melo , Edésio José Tenório de; Gomes, Valdirene Moreira; Cunha, Maura da (Acta Scientiarum. Biological Sciences, 2024)
Among the several native Brazilian plant species that have yet to be studied for their medicinal properties is Verbesina macrophylla, popularly known as “assa-peixe”. The popular use of this species for medicinal purposes has been reported in southeastern Bahia State, with leaf tea being used to treat renal and urethral problems with anti-inflammatory and antifebrile activities, and flower tea to treat inflammation. Despite the potential medicinal importance of V. macrophylla, studies of its chemical composition and possible activity in controlling fungi and parasites are scarce and recent. This study tested the biological activity of aqueous extracts of leaves and inflorescences of V. macrophylla on the yeasts Candida albicans and Candida tropicalis, the filamentous fungus Fusarium oxysporum, and the epimastigote form of Trypanosoma cruzi. Inflorescence extract showed an inhibitory activity of 41% for cells of C. tropicalis, causing changes in the plasma membrane, resulting in fungicidal activity. Both aqueous extracts eliminated epimastigotes with a dose/time-dependent relationship, reaching 100% elimination after treatment with 200 μg mL-1 of either, causing cytoplasmic and nuclear disorganization, vacuolization and enlargement of the reservosomes. Although the studied extracts did not present considerable inhibitory activities against the filamentous fungus and yeasts, promising results were seen with the epimastigote form of T. cruzi. These data add industrial and medicinal value to the species. Additional studies are needed, particularly spectrometric analysis of extracts, to elucidate the metabolite(s) responsible for the results of this study.